Identifikasi Dampak Pengerukan Atau Penggusuran Tanah Tebing di Kelurahan Dorariisa Kecamatan Pulau Hiri Kota Ternate - Alnursa, Darling Surya (Peneliti.net, 2023)
According to Law Number 23 of 1997 concerning Environmental Management, the definition of environmental destruction is an action that causes direct or indirect changes to its physical and/or biological characteristics which result in the environment no longer functioning in supporting sustainable development. One form of environmental destruction is land filling activities and so on. In every development, land acquisition is always a special concern because it always has an impact on the community whose land is being acquired, as well as dredging or eviction of land which also has an impact on the socio-economic conditions of the community affected by the planned activity. The aim of this research is: To identify the impact of dredging or eviction of cliff land in Dorariisa Village, Hiri Island District, Ternate City. By using survey or observation methods with descriptive qualitative research. Most of the people in Dorarisa Village do not agree with the eviction of cliff land, because it results in small-scale landslides that damage roads, even though there are no fatalities. Apart from that, there are often road jams around the cliff land removal area caused by vehicles transporting materials and also because of landslides.